Role of Active Compounds of Bohadschia argus Inhibit Cancer Cell Survival - Souhaly, Jantje Wiliem; Rahayu, Sri; Widodo, Widodo (Graduate School, Universitas Brawijaya, 2019)
Sea cucumber is marine biota with a high economic value and also has potential for anti-cancer. The purpose of this study was to explore the mechanism of active compound of Bohadschia argus on regulating cancer cell survival. The B. argus samples were collected from the sea of Kamal Village, West Seram Maluku, then extracted by water. The constituents of water extract of B. argus were examined by LC-MS. The network among active compound and its protein target were determined by Cytoscape app. The result shows that B. argus has several active compounds, such as chondroitin sulfate, holothurin A, holothurin B, and scabraside that might play a role in cancer cell apoptosis, proliferation, and metastasis. Keywords: Active compound, Bohadschia argus, LC-MS.